For the comfort of Zion : the geographical and theological location of Isaiah 40-55 - Tiemeyer, Lena-Sofia, 1969- (Vetus Testamentum, Supplements, 2011)
This monograph seeks to determine the geographical provenance of Isaiah 40-55. It reassesses past research pertaining to Babylonian influence and reexamines the claims that all or parts of Isaiah 40-55 reflect the concerns of the exilic community in Babylon. It further challenges the prevalent view that the return of the exiles is of central concern in Isaiah 40-55, and instead proposes that Jerusalem and her imminent restoration is its focal point. It interprets Isaiah 40-55 as a polyvalent text that allows multiple and often contradictory views regarding Jerusalem's current suffering. The monograph investigates these views, understood to represent the opinons of different segments of the target audience of Isaiah 40-55, with the aim of determining their geographical and theological locations.